Asuhan Keperawatan Pada Ny. M Keluarga Tn. I Dengan Gangguan Sistem Endokrin: Diabetes Melitus Di Desa Karang Anyar RT 03 RW 04 Kecamatan Tonjong Kabupaten Brebes - Bintang Nur Izzah; Tati Karyawati (STIKES Columbia Asia Medan, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to insufficient insulin production or ineffective insulin utilization. The prevalence of DM in Indonesia reached 11.7% in the 2023 National Health Survey, with Brebes Regency recording 568 DM cases in 2025 and increasing to 157 cases in Tonjong Village in January 2026. This case study aims to describe comprehensive nursing care for Ny. M, a 52-year-old patient diagnosed with endocrine system disorder (diabetes mellitus), in the family of Tn. I at Karang Anyar Village, Tonjong District, Brebes Regency. The method used was a case study with data collection through interview, observation, physical examination, blood glucose measurement, and literature review conducted on December 26–28, 2025. The assessment found subjective data: the patient frequently felt fatigue, tingling in both legs, excessive thirst, and increased urination frequency. Objective data: pale and fatigued face, blood pressure 150/100 mmHg, pulse 95x/min, respiration 22x/min, temperature 36.7°C, and random blood glucose (RBG) 155 mg/dl. Two nursing diagnoses were established: blood glucose instability and readiness for enhanced knowledge. Interventions implemented included hyperglycemia management (monitoring blood glucose, dietary education, complementary herbal therapy with ginger and honey), and health education regarding DM complications. Evaluation results showed that after 2 days of nursing visits, fatigue decreased, blood glucose improved (RBG 130 mg/dl), and the patient's knowledge about DM complications was resolved.